Reconsolidação da memória de extinção : análise farmacológica, bioquímica e molecular - Radiske, Andressa (2015)
Background : Therapies based on the impairment of memory reconsolidation or the enhancement of extinction learning offer the possibility of diminishing the impact caused by the persistent recollection of traumatic events. Nonetheless, the possible interaction between reconsolidation and extinction has rarely been considered. Previously, we reported that reactivation induces reconsolidation of fear extinction, but the molecular bases of this process are largely unknown. Brain-derived neurotrophic factor (BDNF) has been repeatedly linked to fear extinction; therefore we analyzed the possible involvement of this neurotrophin in fear extinction memory reconsolidation. Methods : With a step-down inhibitory avoidance-learning task (IA) and selective pharmacological tools, we investigated the effect of gene expression, protein synthesis and BDNF signaling inhibition on the persistent storage of the reactivated fear extinction memory trace in rats. Results : When given in dorsal CA1 immediately after IA extinction reactivation, the protein synthesis inhibitor anisomycin (ANI), the gene expression inhibitor α- amanitin (AMA), the BDNF maturation blocker PAI-1, and function-blocking anti- BDNF antibody hindered extinction memory persistence. Pro-BDNF and BDNF levels were altered in dorsal CA1 after extinction memory reactivation. Coinfusion of recombinant BDNF reversed the recovery of fear induced by intra-CA1 ANI and AMA. Conclusion : These data suggest that hippocampal BDNF is sufficient to sustain fear extinction memory reconsolidation and indicate that increasing BDNF signaling after extinction memory retrieval impedes the recurrence of fear caused by impairing this process.